Hubungan Self Regulation dengan Perceived Future Employability pada Mahasiswa Tingkat Akhir - Maharani, Tasya; Utami, Rahayu Hardianti (Lembaga Yasin AlSys, 2024)
Perceived future employability is an individual's assessment of skills, experience, connections, personal characteristics, knowledge about the world of work and the reputation of the institution after graduating or graduating, trained and ready to enter the world of work. Self regulation is a person's ability to achieve certain goals, this ability monitors one's own behavior to achieve certain goals or targets including physical, cognitive, emotional and social. The method in this research is quantitative with a correlational research type. The population in this study were final year students at Padang State University. Sampling was carried out using proportional stratified random sampling with a total sample of 331 people. The data analysis technique used is Spearman correlation. Based on the data results obtained, the value r=066 with p=233. So it can be seen that there is a significant positive relationship between self-regulation and perceived future employability in final year students at Padang State University.